(untitled) (Kerala Journal of Psychiatry, 2022)
Background: SARS-CoV-2 virus can affect the lungs and other organs of our body, including the brain. Studies from various parts of the world have started reporting a high prevalence of anxiety disorder in COVID-19 patients. This study aims to estimate the prevalence of generalized anxiety disorder in patients admitted with COVID-19 infection in a tertiary care medical college in South India. Methods: All COVID positive patients admitted to a tertiary care medical college during the study period were evaluated by a psychiatrist, and diagnosis was made based on ICD-10. GAD-7scale was used to assess the severity of anxiety disorder. Results: Hundred and eighty-four COVID-19 patients were studied. Generalized anxiety disorder was detected in 34.8% of the patients. Conclusions: Generalized anxiety disorder is highly prevalent in COVID-19 patients. Proper screening and treating generalized anxiety disorder in them will help in the care of these patients.